Verificação de terceira ordem de estruturas de concreto armado de edíficios - Costa, Ricardo Minozzi [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The change in design of a building can occur during its construction process, especially when this change involves greater amount of profit for the building company, as it is the case of adding extra floors. However, there must be an analysis of the structure of the building in order to see if it is possible to increase the number of floors without the need of reinforcement, as this need would result in higher costs for the building company. This graduation report presents this analysis by using the methods of third order verification of reinforced concrete structures

A mudança de projeto de um edifício pode ocorrer durante seu processo construtivo. Especialmente quando esta mudança envolve maior lucro para a construtora, como é o caso de acréscimo de pavimentos. Porém, deve ser feita uma análise da estrutura do edifício para verificar se é possível aumentar o número de pavimentos sem necessidade de reforço, já que isto acarretaria em maiores gastos para a construtora. Este trabalho de graduação apresenta esta análise através dos métodos da verificação de terceira ordem de estruturas de concreto armado de edifícios
Keywords: Teoria das estruturas; Concreto armado; Edificios; Structural analysis